2022 IEEE/CVF Winter Conference on Applications of Computer Vision (WACV) 2022
DOI: 10.1109/wacv51458.2022.00201
|View full text |Cite
|
Sign up to set email alerts
|

Robust Lane Detection via Expanded Self Attention

Abstract: The image-based lane detection algorithm is one of the key technologies in autonomous vehicles. Modern deep learning methods achieve high performance in lane detection, but it is still difficult to accurately detect lanes in challenging situations such as congested roads and extreme lighting conditions. To be robust on these challenging situations, it is important to extract global contextual information even from limited visual cues. In this paper, we propose a simple but powerful self-attention mechanism opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…The proposed RIL framework can be easily plug-and-play in most cutting-edge methods without any extra inference cost. Experimental results prove the eectiveness of RIL framework both on CULane [23] and TuSimple [33] for four modern lane detection methods including UFAST [26], ERFNet [27], ESA [11] and Cond-LaneNet [14] respectively.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…The proposed RIL framework can be easily plug-and-play in most cutting-edge methods without any extra inference cost. Experimental results prove the eectiveness of RIL framework both on CULane [23] and TuSimple [33] for four modern lane detection methods including UFAST [26], ERFNet [27], ESA [11] and Cond-LaneNet [14] respectively.…”
Section: Introductionmentioning
confidence: 80%
“…In this section, we rst briey introduce the overview framework of our proposed RIL and then illustrate each module in RIL. Note that our method can be exibly combined with many cutting-edge lane detection methods such as [11,14,26,27]. In this section, we adapt ERFNet [27] to RIL framework for a demonstration.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Deep methods built by convolutions have exploded in recent years, making significant progress and applicable systems for real applications (Chen et al 2018;Zhao, Yuan, and Chen 2020). Two-stage methods which extract segmentation or proposal plus post-processing ruled the filed for several years (Neven et al 2018;Philion 2019;Pan et al 2018;Zhang et al 2018;Hou et al 2019;Ko et al 2020;Li et al 2020;Tabelini et al 2021;Qin, Wang, and Li 2020;Xu et al 2020;Jung et al 2020;Yoo et al 2020;Lee et al 2021;Zheng et al 2020). To streamline the pipeline into an endto-end fashion, single-stage methods (Torres et al 2020;Liu et al 2021) directly estimate coefficients of prior mathematical curves have shown both higher efficacy and efficiency.…”
Section: Related Workmentioning
confidence: 99%
“…With the evolution of advanced assisted driving system and automatic driving technology, the road accident probability is greatly reduced and the driving safety is improved [ 1 , 2 , 3 , 4 ]. As a key and challenging part of automatic driving and advanced assistant system, lane detection has also become a research hotspot [ 5 , 6 , 7 , 8 ]. It is vital for driver assistance systems to obtain the accurate location of each lane, which is also the goal of the lane detection algorithm.…”
Section: Introductionmentioning
confidence: 99%